Levosimendan to Facilitate Weaning From Cardiorespiratory Support in Critically Ill Patients: A Meta-Analysis - Luo, Jing-Chao; Zheng, Wen-He; Meng, Chang; Zhou, Hua; Xu, Yuan; Tu, Guo-Wei; Luo, Zhe; Huang, Hui-Bin (Frontiers in Medicine, 2021)
Background: Cardiopulmonary support, as extracorporeal membrane oxygenation (ECMO) or mechanical ventilation (MV), is crucial for ICU patients. However, some of these patients are difficult to wean. Therefore, we aimed to assess the efficacy and safety of levosimendan in facilitating weaning from cardiorespiratory support in this patient population. Methods: We searched for potentially relevant articles in PubMed, Embase, China National Knowledge Infrastructure, Wanfang, and the Cochrane database from inception up to Feb 30, 2021. Studies focusing on weaning data in MV/ECMO adult patients who received levosimendan compared to controls were included. We used the Cochrane risk of bias tool or the Newcastle-Ottawa Quality Assessment Scale to evaluate the study quality. The primary outcome was the weaning rate from MV/ECMO. Secondary outcomes were mortality, duration of MV, and ICU stay. Subgroup analysis, sensitivity analysis, and publication bias were also conducted. Results: Eighteen studies with 2,274 patients were included. The quality of the included studies was low to moderate. Overall, levosimendan effectively improved weaning rates from MV/ECMO (odds ratio[OR]=2.32; 95%CI, 1.60-3.36; P<0.00001, I2=68%). Subgroup analyses confirmed the higher successful weaning rates in ventilated patients with low left ventricular ejection fractions (OR=4.06; 95%CI, 2.16-7.62), patients with ECMO after cardiac surgery (OR=2.04; 95%CI, 1.25-3.34), and patients with ECMO and cardiogenic shock (OR=1.98; 95%CI, 1.34-2.91). However, levosimendan showed no beneficial effect on patients with MV weaning difficulty (OR=2.28; 95%CI, 0.72-7.25). Additionally, no differences were found concerning the secondary outcomes between the groups. Conclusions: Levosimendan therapy significantly increased successful weaning rates in patients with cardiopulmonary support, especially patients with combined cardiac insufficiency. Large-scale, well-designed RCTs will be needed to define the subgroup of patients most likely to benefit from this strategy.